The first report on the state of the world's animal genetic resources coordinated by FAO. Progress and resources - Cardellino R. (Breeding programmes for improving the quality and safety of products. New traits, tools, rules and organization?, 2003)
This paper describes the goals, components, costs and sources of funding for the First Report on the State of the World's Animal Genetic Resources coordinated by FAO and to be implemented between 1999 and 2006.
Meeting of the Sub-Network on Genetic Resources of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2002/05/9-11, Sassari (Italy)